SUBJECT SPECIFIC PAEDAGOGIC (SSP) BASED ON HIGHER ORDER THINKING SKILL (HOTS) TO IMPROVE THE ABILITY OF SD TEACHERS IN SURAKARTA - Siti Istiyati; Kartono Kartono; Idam Ragil Widianto Atmojo (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this service is to train elementary school teachers in the administrative area of Surakarta city to have capabilities that are in accordance with the times or disruption era. In detail, the aim of this activity is to improve the ability of teachers to develop high order-based specific pedagogic (SSP) subjects. thinking skill (HOTs). The subject of this service is an elementary school teacher in the city of Surakarta. The method used in this service begins the Workshop, Practices, and Implementation. In conducting this training the subjects were asked to work on tests related to the development of the SSS based HOTs. Analysis of the data used is pre-test and post-test. The result of this activity is that there is an increase in the knowledge and understanding of teachers regarding the development of SSS based on HOTs